2022
DOI: 10.1021/acssuschemeng.2c04249
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Electrocatalytic Nitrate-to-Ammonia Conversion via Plasma Enhanced CuCo Alloy–Substrate Interaction

Abstract: Electrocatalytic conversion of widely distributed nitrate from industrial wastewater into value-added ammonia was proposed as an attractive and sustainable alternative to harvesting green ammonia. Herein, CuCo alloys were facilely synthesized for nitrate conversion, while nonthermal Ar-plasma was employed to enhance the adhesion strength between the electrocatalyst and substrate interface via regulating the surface hydrophobicity and roughness. Based on Ar-plasma treatment, a high ammonia yield rate (5129.29 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Electrochemical approaches have been proposed to recover nitrogen nutrients by driving the thermodynamically favorable NO 3 – to NH 3 conversion instead of reducing it to N 2 . , Therefore, electrocatalytic NO 3 – reduction to NH 3 has been extensively investigated in recent work. The performances of metallic (Ti, Cu, Co, , Ru, Ni, Fe, and Bi) and bimetallic (CuCo, CuNi, , and CuPd ) electrocatalysts have been reported at various pH levels and NO 3 – concentrations. Deng et al (pH 14) and Kani et al (pH 7 and 14) demonstrated >90% Faradaic efficiency for NH 3 production on Co catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical approaches have been proposed to recover nitrogen nutrients by driving the thermodynamically favorable NO 3 – to NH 3 conversion instead of reducing it to N 2 . , Therefore, electrocatalytic NO 3 – reduction to NH 3 has been extensively investigated in recent work. The performances of metallic (Ti, Cu, Co, , Ru, Ni, Fe, and Bi) and bimetallic (CuCo, CuNi, , and CuPd ) electrocatalysts have been reported at various pH levels and NO 3 – concentrations. Deng et al (pH 14) and Kani et al (pH 7 and 14) demonstrated >90% Faradaic efficiency for NH 3 production on Co catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…5,10−12 Therefore, electrocatalytic NO 3 − reduction to NH 3 has been extensively investigated in recent work. The performances of metallic (Ti, 13 Cu, 14−22 Co, 23,24 Ru, 25 Ni, 26 Fe, 27 and Bi 28 ) and bimetallic (CuCo, 29 CuNi, 30,31 and CuPd 32−34 ) electrocatalysts have been reported at various pH levels and NO 3 − concentrations. Deng et al 23 Kani et al 24 (pH 7 and 14) demonstrated >90% Faradaic efficiency for NH 3 production on Co catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12–14 ] As nitric oxide (NO) is one of the major nitrogeneous pollutants abundant in fossil fuel combustion and other chemical industry, [ 15,16 ] the rational utilization of waste NO via electrocatalysis can simultaneously alleviate the environmental load and reverse the anthropogenically global nitrogen cycle imbalance. [ 17–19 ] For efficient electrocatalytic NO reduction reaction (NORR), the Cu‐based catalyst has been validated theoretically and experimentally. [ 20 ] Nevertheless, it still suffers from high overpotential and competitive HER, which could be optimized by further modification such as transition metal (oxide) deposition.…”
Section: Introductionmentioning
confidence: 99%
“…global nitrogen cycle imbalance. [17][18][19] For efficient electrocatalytic NO reduction reaction (NORR), the Cu-based catalyst has been validated theoretically and experimentally. [20] Nevertheless, it still suffers from high overpotential and competitive HER, which could be optimized by further modification such as transition metal (oxide) deposition.…”
mentioning
confidence: 99%
“…Transitional metals (Cu, Co, Ni, and Fe) have been used as catalysts for nitrate reduction. ,, However, they usually catalyze at highly negative applied potentials (such as < −0.4 V vs RHE), which is energetically inefficient for future applications. Designing heterostructures such as metal/carbon hybrids can efficiently facilitate electron transfer and endow the structures with a large number of stable electrochemical active sites. , Metal–organic frameworks (MOFs) have attracted substantial interest owing to their tailorable derived heterostructures, compositional flexibility and the ability to form porous carbon frameworks. These merits make the synthesis of hybrids comprising alloying metals highly feasible.…”
Section: Introductionmentioning
confidence: 99%